2011
DOI: 10.1002/ejoc.201001677
|View full text |Cite
|
Sign up to set email alerts
|

Triazolyl Derivatives for Acidic Release of Alcohols

Abstract: New triazolyl-based carbonates and ethers have been investigated as potential alcohol-releasing systems under mild acidic conditions. Triazolyl carbonates could not be prepared because of their apparent instability, whereas ethers were successfully obtained. The rate of hydrolysis of these ethers ramged from a few hours to several days. A theoretical investigation demonstrated that the acidic release of alcohols from triazole derivatives proceeds first by protonation of the tri-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Our linker system is comprised of a diamine-derived cyclisation spacer 14 connected in series to a triazole 1,4-elimination spacer ( Scheme 1 ). 16 Incorporating a diamine-derived spacer next to the triazole ring permits the use of carbamate trigger groups, 17 which drastically expands the scope of ester triggers reported previously. 18 Removal of the trigger group from 1 under basic conditions exposes a secondary amine nucleophile ( 2 ) that undergoes a cyclisation–elimination reaction to afford a cyclic urea ( 3 ) and a short-lived triazolyl-1-methanol species.…”
Section: Resultsmentioning
confidence: 99%
“…Our linker system is comprised of a diamine-derived cyclisation spacer 14 connected in series to a triazole 1,4-elimination spacer ( Scheme 1 ). 16 Incorporating a diamine-derived spacer next to the triazole ring permits the use of carbamate trigger groups, 17 which drastically expands the scope of ester triggers reported previously. 18 Removal of the trigger group from 1 under basic conditions exposes a secondary amine nucleophile ( 2 ) that undergoes a cyclisation–elimination reaction to afford a cyclic urea ( 3 ) and a short-lived triazolyl-1-methanol species.…”
Section: Resultsmentioning
confidence: 99%
“…These results also indicated that the hydroxamic acid pro-drugs are more stable than the benzamide ones for the same R group. Pro-drugs of alcohols like uridine were also previously evaluated and are even more stable, where the best system is the dimethoxyphenyl 5c for a convenient half-life of 6-7 h at pH 5 [26].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of pro-drugs (Scheme 1), the determination of the hydrolysis rates of pro-drugs in mildly acidic pH [25,26], the pro-drug-functionalized macromonomer-PEO-CI994 (17), the pro-drug-functionalized macro-monomer-PEO-SAHA (16), the pro-drug-functionalized macro-monomer-PEO-NODH (15), and the synthesis of the pro-drug functionalized nanoparticles (NPs) (Figure 1), and the biological tests are developed in the supporting information part.…”
Section: Discussionmentioning
confidence: 99%
“…3 Covalent acid-sensitive linkers are used to connect drugs to vectors 4 to exploit the acidic process of endocytosis. We recently described amine 5 and alcohol 6 release (Scheme 1, X = NH or O respectively) based on an acid-sensitive triazolyl system obtained by click chemistry 7 and report herein new findings for the release of aniline.…”
mentioning
confidence: 97%